A thirst for empire : how tea shaped the modern world - Rappaport, Erika Diane, 1963- (Princeton, NJ : Princeton University Press, 2017)
"Tea has been one of the most popular commodities in the world. Over centuries, profits from its growth and sales funded wars and fueled colonization, and its cultivation brought about massive changes--in land use, labor systems, market practices, and social hierarchies--the effects of which are with us even today. A Thirst for Empire takes a vast and in-depth historical look at how men and women--through the tea industry in Europe, Asia, North America, and Africa--transformed global tastes and habits and in the process created our modern consumer society. As Erika Rappaport shows, between the seventeenth and twentieth centuries the boundaries of the tea industry and the British Empire overlapped but were never identical, and she highlights the economic, political, and cultural forces that enabled the British Empire to dominate--but never entirely control--the worldwide production, trade, and consumption of tea. Rappaport delves into how Europeans adopted, appropriated, and altered Chinese tea culture to build a widespread demand for tea in Britain and other global markets and a plantation-based economy in South Asia and Africa. Tea was among the earliest colonial industries in which merchants, planters, promoters, and retailers used imperial resources to pay for global advertising and political lobbying. The commercial model that tea inspired still exists and is vital for understanding how politics and publicity influence the international economy ..."--Jacket.
Introduction : A soldiers' tea party in Surrey -- Part I. Anxious relations. "A China drink approved by all physicians" : setting the early modern tea table -- The temperance tea party : making a sober consumer culture in the nineteenth century -- A little opium, sweet words, and cheap guns : planting a global industry in Assam -- Packaging China : advertising food safety in a global marketplace -- Part II. Imperial tastes. Industry and empire : manufacturing imperial tastes in Victorian Britain -- The planter abroad : building foreign markets in the fin de siècle -- "Every kitchen an empire kitchen" : the politics of imperial consumerism -- "Tea revives the world" : selling vitality during the Depression -- "Hot drinks means much in the jungle" : tea in the service of war -- Part III. Aftertastes. Leftovers? : an imperial industry at the end of empire -- "Join the tea set" : youth, modernity, and the legacies of empire during the swinging sixties.
Includes bibliographical references (pages 411-527) and index.
JSTOR
Keywords: Tea -- History; Tea -- Social aspects -- History; Imperialism -- Social aspects -- History; History, Modern; Impérialisme -- Aspect social -- Histoire; Histoire moderne et contemporaine; COOKING -- General; HISTORY / Asia / China; History, Modern; Imperialism -- Social aspects; Tea; Tea -- Social aspects; History